The last words of Will Wolfkin - Knight, Steven 1959- (Walden Pond Press / HarperCollins, 2010)
Fourteen-year-old Toby, paralyzed since birth and raised in a convent, suddenly finds himself capable of movement and speech when his long-time companion, a cat, takes him on a magical and mysterious journey to Iceland
Keywords: Adventure and adventurers / Fiction; Magic / Fiction; Human-animal relationships / Fiction; Identity / Fiction; Paralysis / Fiction; Cats / Fiction; Adventure stories; Identity (Philosophical concept) / Fiction; Fantastischer Roman; Reise; Lähmung; Katze; Königreich; Magie; Männliche Jugend -- 14-16 Jahre; Einzelgänger; Iceland / Fiction; Island; Jugendbuch